2013
DOI: 10.1637/10356-091012-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Levels of Very Virulent MDV in Poultry Dust and in Feather Tips from Vaccinated Chickens

Abstract: SUMMARY. To assess the effect of various vaccine strains on replication and shedding of virulent Marek's disease virus from experimentally infected chickens, quantitative PCR (q-PCR) methods were developed to accurately quantify viral DNA in infected chickens and in the environment in which they were housed. Four groups of 10 chickens, kept in poultry isolators, were vaccinated at 1 day old with one of four vaccines covering each of the three vaccine serotypes, then challenged with very virulent MDV strain Md5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…7a-c). This suggests that measurements of MDV load in feathers and dust are measuring MDV in different cell populations or with a different efficiency, despite the high correlation between measurements of MDV in dust and feather tips reported elsewhere (Baigent et al, 2013). When only positive samples were analysed (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…7a-c). This suggests that measurements of MDV load in feathers and dust are measuring MDV in different cell populations or with a different efficiency, despite the high correlation between measurements of MDV in dust and feather tips reported elsewhere (Baigent et al, 2013). When only positive samples were analysed (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…However, early and large reductions in MDV load due to vaccination are detected in feather tips which runs counter to this, and raises the issue of the relationship between measures of MDV in feather tips (including a heterogeneous cell population in feather pulp) and those in dust. In the only study directly examining this issue, a close association was reported (Baigent et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…In practice, we used N = 5 incubation classes with a transition rate β chosen to produce virus shed rates over time that were consistent with average viral copy number in feather tips of experimentally infected birds (Read et al, 2015), which is strongly correlated with viral shedding intensity (Baigent et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The substantial improvement of sequencing techniques has also allowed the direct sequencing of viral DNA extracted from feather tips to detect coinfections for instance [56]. Moreover, PCR methods allow the detection and quantification of viral DNA in dust collected and concentrated on filters [51,57,58]. Finally, MDV can also be re-isolated from feather pulp via co-culture in vitro [14].…”
Section: Methods For MDV Detection In the Skin Or Feathers (Diagnomentioning
confidence: 99%